2003
DOI: 10.1038/sj.bjp.0705315
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cyclooxygenase inhibitor pretreatment on nitric oxide production, nNOS and iNOS expression in rat cerebellum

Abstract: 1 The therapeutic effect of nonsteroidal anti-inflammatory drugs (NSAIDs) is thought to be due mainly to its inhibition of cyclooxygenase (COX) enzymes, but there is a growing body of research that now demonstrates a variety of NSAIDs effects on cellular signal transduction pathways other than those involving prostaglandins. 2 Nitric oxide (NO) as a free radical and an agent that gives rise to highly toxic oxidants (peroxynitrile, nitric dioxide, nitron ion), becomes a cause of neuronal damage and death in som… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
18
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 23 publications
(36 reference statements)
2
18
0
1
Order By: Relevance
“…Minocycline acts as an inhibitor of microglial activation and has previously been shown to reduce iNOS expression, e.g., in global brain ischemia (58) or in a model of Huntington's disease (9). Indomethacin also reduced iNOS upregulation in cerebellar homogenates of LPS-treated rats (11). However, additional mediators may be involved in the modulation of neurogenesis in the context of inflammation.…”
Section: Discussionmentioning
confidence: 95%
“…Minocycline acts as an inhibitor of microglial activation and has previously been shown to reduce iNOS expression, e.g., in global brain ischemia (58) or in a model of Huntington's disease (9). Indomethacin also reduced iNOS upregulation in cerebellar homogenates of LPS-treated rats (11). However, additional mediators may be involved in the modulation of neurogenesis in the context of inflammation.…”
Section: Discussionmentioning
confidence: 95%
“…Consequently, the production of cytokines secreted by macrophages at the injury site is hampered, reducing the inflammatory response (Rainsford, ). Furthermore, researchers have shown that ibuprofen reduces the activity of inducible isoform of nitric oxide synthase, which produces changes in transmembrane ion flux (Liles & Flecknell, ) and is also involved in inflammatory processes (Di Girolamo et al., ). Interestingly, a study described by Da Silva et al.…”
mentioning
confidence: 99%
“…NSAIDs such as indomethacin and ibuprofen also reduce cytokineactivated iNOS mRNA in a murine macrophage cell line [Ogawa et al, 2000]. NSAIDs such as indomethacin and lysine clonixinate also attenuate LPS-induced iNOS expression in vivo [DiGirolamo et al, 2003]. However, the attenuating effects of NSAIDs on NO may also contribute to the adverse side effects on the gastric mucosal tissue, with long-term administration.…”
Section: Discussionmentioning
confidence: 98%